Formulasi Patch Bukal Mukoadhesif Isosorbid Dinitrate dengan Variasi Konsentrasi PVP-K29 dan CMC-Na - Ayu Diah Sukmasih; Mufrod Mufrod; Siti Aisiyah (Jurnal Farmasi Indonesia, 2014)
Buccal patch is a preparation used to put on the buccal mucosa so that issues such as first-pass metabolism, avoid pre-elimination systemic GI tract can be overcome. Isosorbide dinitrate is nitrate which used for anti angina, inside of administration through the oral only have bioavailability 29% and overhauled in the liver, time half-life 45-60 minutes. This study used isosorbide dinitrate in buccal patch with various concentrations of CMC-Na and PVP-K29 as a matrix, to determine the physical properties and release kinetics of isosorbide dinitrate. Physical properties test were weight uniformity, folding endurance, surface pH, swelling index and uniformity of content. In vitro release using USP Type II method of rotating paddle speed of 50 rpm with the dissolution medium aqua bidestilata 500 ml. High performance liquid chromatography used UV detector 220 nm, mobile phase methanol pro HPLC and aqua (50:50). The results showed that the ratio of 30:70 showed the results of swelling index minutes of 180 326.268%, dissolution percent minutes 480 90.625% follow the kinetics of zero order by diffusion.